Knowledge, attitude and practice of post-natal exercises among post-natal women from a tertiary care centre, South India - Sundaramurthy, Raja; Kathiresan, Sasikala; Venkateshvaran, Sriandaal; Kannan, Surya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Stressful puerperal period and its complications can be prevented by adequate care, proper diet and exercises. Though studies have indicated post-natal exercises (PNE) is helpful in reducing the effect of perineal muscle weakness, many women are unaware of its full benefits. This study is planned to know the knowledge, attitude and practice of PNE in post-natal mothers. Methods: Descriptive cross-sectional study was conducted in department of obstetrics and gynecology for 3 months (November 2019 to January 2020). 160 post-natal women were enrolled with convenient sampling. Structured questionnaire was used to collect socio-demographic and obstetric details, source of information, knowledge, attitude and practice of PNE. Results: A total 58.8% of this study participants revealed health care professions were the commonest source of information. More than half of them had adequate knowledge but still many were not aware of full benefits of PNE as only 3-5% aware of other benefits like prevention of urinary incontinence. 98.8% of the women’s felt PNE is essential and 62.5% felt household work hinder them doing. 92.5% said they will emphasize the importance of PNE to others. No significant correlation found between socio-demographic characters and knowledge, attitude and practice of PNE. Conclusions: Though most of the study population had adequate knowledge and positive attitude, household activities were the commonest barrier in doing PNE. Educating and creating awareness among family members is essential to improve the adherence. Continuing influence by health care workers during antenatal and postnatal period will be the key for improving adherence.